Sugar esterification catalysed by alkylated trypsin in dimethylformamide - Ampon, K.; Salleh, A.B.; Teoh, A.; Wan Yunus, W.M.Z. (Kluwer Academic Publishers, 1991)
Reductive alkylation of porcine pancreatic trypsin with acetaldehyde, propionaldehyde, octaldehyde and benzaldehyde resulted in about 5 to 6 folds increase in the sugar esterification activities of the enzyme in DMF. The optimum activities of the modified enzymes depend on the degrees of their modification with the respective aldehydes. These alkylated trypsins were more stable in DMF compared to the native unmodified enzyme at temperatures between 26 and 60°C. © 1991 Kluwer Academic Publishers.